Swimming against the tide : how developing countries are coping with the global crisis (World Bank [Washington]US, 2009)
Looks at the impact on the poor and most vulnerable, policy challenges in responding to the crisis and ways of limiting the damage from the crisis. Deals with ways in which the World Bank is helping and identifies urgent priorities.
Keywords: ECONOMIC RECESSION